IMPLEMENTASI PRAKTIK PEMBUATAN GAME EDUKATIF BERBASIS SCRATCH UNTUK MENINGKATKAN KEAKTIFAN SISWA PADA PEMBELAJARAN KKA - Mustina Saputri; Argia Wardana; Nursiah; Aisha; Emmi Azis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of Scratch-based educational game creation practices in Coding and Artificial Intelligence (KKA) learning to improve student activeness. The background of this research is based on the low level of student participation during the learning process, which is still dominated by conventional teaching methods and limited use of interactive learning media. Therefore, the integration of Scratch as a technology-based learning medium is expected to create a more engaging, interactive, and enjoyable learning environment for students. This research employed a descriptive qualitative approach focusing on the direct practice of designing educational games using Scratch in classroom learning activities. The study was conducted at UPT SMAN 9 Bone during the implementation of the PLP II program in the 2025/2026 academic year. Data collection techniques included observation and documentation of students’ activities during the learning process. The findings revealed that the implementation of Scratch-based educational game practices significantly increased student activeness, which was reflected in students’ participation, interaction, creativity, enthusiasm, and involvement during learning activities. Furthermore, Scratch-based learning created a more interactive classroom atmosphere that encouraged students to actively engage in discussions, ask questions, and complete project-based assignments collaboratively. Thus, the implementation of Scratch-based educational game practices can be effectively utilized as an alternative interactive learning strategy to improve student activeness in Coding and Artificial Intelligence (KKA) learning.